АБАЙ ОБЛЫСЫНДАҒЫ ШАҒЫН КӨЛДЕР БАЛЫҚТАРЫНЫҢ ГЕМАТОЛОГИЯЛЫҚ ЖӘНЕ РАДИОЭКОЛОГИЯЛЫҚ КӨРСЕТКІШТЕРІН ИХТИОПАТОЛОГИЯЛЫҚ БАҒАЛАУ. - А. Кенжебекова; Е. Билялов; Д. Зайнеттинова; О. Зайковская; А. Берікқалиева; А. Қожаева; Б. Сатыбаев; А. Ниятова (Animal Health and Biosafety, 2026)
The assessment of the ecological status of small lake ecosystems in the Abai Region represents one of the important directions of contemporary veterinary and ichthyopathological research. In recent years, the increasing anthropogenic and technogenic pressure on aquatic ecosystems has led to deterioration in water quality, disruption of hydrochemical balance, and alterations in the physiological condition of aquatic bioresources. Such ecological changes may contribute to the development of stress factors in fish organisms, immunological instability, and the formation of various pathological processes. In this regard, the comprehensive investigation of hematological, hydrochemical, parasitological, and radioecological indicators in fish is considered an important component of veterinary monitoring. The aim of the study was to assess the ichthyopathological condition of fish inhabiting small lakes in the Abai Region through the investigation of hematological and radioecological indicators, as well as to determine the impact of environmental factors on fish organisms. The research was conducted during 2025-2026. Freshwater fish species including Abramis brama, Cyprinus carpio, and Carassius auratus were selected as the study objects. A total of 120 fish samples were included in the study. Hematological analysis involved the determination of erythrocyte count (RBC), hemoglobin level (HGB), hematocrit value (HCT), and leukocyte count (WBC). Hydrochemical analysis of water samples was performed to evaluate water temperature, pH, dissolved oxygen concentration, and ammonium and nitrite levels. In addition, parasitological and histopathological examinations were carried out. The results of the study demonstrated a decrease in erythrocyte count and hemoglobin concentration in lakes subjected to higher anthropogenic pressure. Furthermore, an increase in leukocyte count indicated the activation of protective and adaptive reactions in fish organisms. Hydrochemical analysis revealed reduced dissolved oxygen levels and elevated ammonium concentrations. Parasitological examinations showed an increased prevalence of parasitic infestations. Histopathological analysis identified inflammatory and dystrophic alterations in liver and kidney tissues. Future studies are planned to further investigate the concentrations of heavy metals in water bodies, the accumulation levels of radionuclides, and the biochemical parameters of fish.